Beat Gestures for Comprehension and Recall: Differential Effects of Language Learners and Native Listeners - Rohrer, Patrick Louis; Delais-Roussarie, Elisabeth; Prieto, Pilar (Frontiers in Psychology, 2020)
Previous work has shown how native listeners benefit from observing iconic gestures during speech comprehension tasks of both degraded and non-degraded speech. By contrast, effects of the use of gestures in non-native listener populations are less clear. The current study aims to complement these findings by testing the potential beneficial effects of beat gestures (non-referential gestures which are often used for information- and discourse marking) on language recall and comprehension of a narrative task by both native and non-native listeners. The experimental design will allow to directly compare the effects of beat gestures on natural discourse processing in the participant’s native to their non-native language. Using a within-subject design, 51 French intermediate learners of English participated in a narrative-drawing task. Each participant was assigned 8 videos to watch, where a native speaker describes the events of a short comic strip. Videos were presented in random order, in four conditions: in Native listening conditions with frequent, naturally-produced beat gestures, in Native listening conditions without any gesture, in Non-native listening conditions with frequent, naturally-produced beat gestures, and in Non-native listening conditions without any gesture. Participants watched each video twice and then immediately recreated the comic strip through their own drawings. Participants’ drawings were then evaluated for comprehension (via their ability to convey the main goals of the narrative through their drawings) and recall (via the number of gesturally-marked details in the narration that were included in their drawings). Results showed that for native listeners, beat gestures had no significant effect on either recall or comprehension. In non-native speech, however, beat gestures led to significantly lower comprehension and recall scores. These results suggest that frequent, naturally-produced beat gestures in longer discourses may increase cognitive load for language learners, resulting in negative effects on both memory and language understanding. These findings add to the growing body of literature that suggests that gesture benefits are not a “one-size-fits-all” solution, but rather may be contingent on factors such as language proficiency and gesture rate, particularly in that whenever beat gestures are repeatedly used in discourse, they inherently lose their saliency as markers of important information.